Perceiving Sound Objects in the Musique Concrète - Godøy, Rolf Inge (Frontiers in Psychology, 2021)
In the late 1940s and early 1950s, there emerged a radically new kind of music based on recorded environmental sounds instead of sounds of traditional Western musical instruments. Centered in Paris around the composer, music theorist, engineer, and writer Pierre Schaeffer, this became known as musique concrète because of its use of concrete recorded sound fragments, manifesting a departure from the abstract concepts and representations of Western music notation. Furthermore, the term sound object was used to denote our mental images of such fragments. Sound objects and their features became the focus of an extensive research effort on the perception and cognition of music in general, remarkably anticipating topics of more recent music psychology research. This sound object theory makes extensive use of metaphors, often related to motion shapes, and these metaphors and shape concepts can provide holistic representations of perceptually salient, but temporally distributed, sound object features in many different kinds of music.